2019
DOI: 10.21203/rs.2.13537/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patients’ Satisfaction with Clinical Laboratory Services in Public Hospitals in Ethiopia

Abstract: Background: Knowing customers’ level of satisfaction is relevant to improve and provide quality health care services. In the clinical laboratory, monitoring customers’ satisfaction is an important indicator of the quality management system and required by international laboratory standards. However, in Ethiopia, there has not been baseline data about the satisfaction level of patients’ with laboratory services at the national level. The aim of this national level survey was to assess patients’ satisfaction le… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…Indeed, what was stated by the patients more re ect the realities of the patient-practitioner communication as it conforms to the researcher's observational data. The 50.6% of patients who were not informed about the testing turnaround time as found by this study is however lower than the 88% reported in a national survey in Ethiopia (13). Incidentally, majority of the individuals who reported knowing their respective testing turnaround times were those undertaking blood chemistries.…”
Section: Discussioncontrasting
confidence: 77%
“…Indeed, what was stated by the patients more re ect the realities of the patient-practitioner communication as it conforms to the researcher's observational data. The 50.6% of patients who were not informed about the testing turnaround time as found by this study is however lower than the 88% reported in a national survey in Ethiopia (13). Incidentally, majority of the individuals who reported knowing their respective testing turnaround times were those undertaking blood chemistries.…”
Section: Discussioncontrasting
confidence: 77%
“…As such, satisfaction contains the person’s appraisal, which includes both affective (or emotional) and cognitive (evaluative) components [ 14 , 15 ]. Health consumer satisfaction is a unique structure, distinct from regular customer satisfaction since healthcare services have a major impact on physical wellbeing [ 16 , 17 ]. Hence, a bad service experience in the healthcare context is more threatening than a bad service experience in general, as it might constitute a life threat [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Waiting times are soaring globally, while satisfaction with hospital visits is dropping. Therefore, if patients' waiting times could be shortened, satisfaction levels with such systems (and even the overall medical experience) can be greatly improved [68].…”
Section: A Principal Findingsmentioning
confidence: 99%